The presence of female painters in Barcelona exhibitions (1888-1936) - Reguant Montiel, Blanca; Urbano Lorente, Judith; Fuentes Milà, Sergio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article explains the current research of a doctoral dissertation with title “The presence of female painters in Barcelona exhibitions (1888-1936)” whose objective is to quantify the participation of women artist in individual and collective exhibitions in the city and to analyze the social relevance that they obtained and their critical fortune from their reception of the public and the critics at the epoque.